Studi Kelayakan Bisnis Usaha Makanan Tradisional Berbahan Alami Permen Santan Tagih - Dini Vientiany; Annisa Hafsah; Khoirunnisya Gita Segara; Said Luthfi Ramadhan (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Micro, small, and medium enterprises (MSMEs) producing traditional food products made from natural ingredients play an important role in the local economy and the preservation of traditional cuisine. However, most traditional food MSMEs are still run without comprehensive business feasibility analysis, so that business development is often not based on a systematic evaluation of market, technical, resource, and business risk aspects. The limited empirical studies that integrate non-financial feasibility aspects in household-scale traditional food MSMEs indicate a research gap. This study aims to analyze the feasibility of the natural ingredient-based traditional food business Permen Santan Tagih through a business feasibility study approach. The research method used is descriptive qualitative with observation and in-depth interview techniques, supported by literature studies. The analysis was conducted on the aspects of market and marketing, technical and production, raw materials, human resources, and business risks. The results of the study indicate that the business has stable market opportunities, supported by a multi-channel marketing strategy and product differentiation, a production process that is consistent with natural raw materials, a relatively guaranteed availability of raw materials, and efficient workforce management. Business risks remain at a manageable level. Overall, the Tagih Coconut Candy business is considered feasible to operate and develop sustainably with strengthened production management, digital marketing, and business risk mitigation.